(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
In this research paper, ambitious goals and the significant importance of artificial intelligence (AI) in improving quality of life and enhancing efficiency across various domains were reviewed. The study aimed to drive the development of new capabilities within the marketing team in the field of AI, bringing together data experts and understanding the potential of emerging technologies in the studied domain. Embracing radical changes due to the emergence and evolution of AI, many companies have leveraged these tools to succeed in their online marketing endeavors. By gaining a deeper understanding of the fundamental principles and applications of AI, the study explored the vital role AI plays in transforming financial and administrative processes at Al-Rafidain Bank. Advanced technologies, such as expert systems and AI-driven analytics, enable the analysis of massive datasets, pattern discovery, and relationship identification, empowering the bank to make informed financial decisions and offer innovative services to customers. The results demonstrate that AI enhances the efficiency of banking operations, improves investment decisions, and provides more accurate future predictions. Additionally, it helps alleviate burdens on beneficiaries, enhances security, and offers effective solutions to contemporary challenges. Al-Rafidain Bank’s expansion through AI applications contributes to achieving a competitive advantage by reducing the cost of banking services and enhancing their quality, ultimately increasing market share. However, the bank faces challenges in adopting these technologies, necessitating a delicate balance between innovation, security, and privacy. In the end, AI represents the future of the banking sector, and Al-Rafidain Bank is steadily progressing toward realizing this future, leveraging opportunities and addressing challenges adeptly. The study recommends further research in this field, given its need for more modifications and investigations, especially as the modern world gravitates toward AI. Training personnel responsible for AI implementation before expanding the bank’s use of these applications is crucial. Establishing a dedicated AI unit to keep pace with its rapid evolution is also essential. Finally, emphasizing AI adoption and utilizing various forms of software, algorithms, and expert systems will facilitate most operations within Al-Rafidain Bank.